2011
DOI: 10.1007/s10637-011-9711-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel dichlorophenyl urea compounds inhibit proliferation of human leukemia HL-60 cells by inducing cell cycle arrest, differentiation and apoptosis

Abstract: Two novel dichlorophenyl urea compounds, SR4 and SR9, were synthesized in our laboratory and evaluated for anti-cancer activities. Specifically, we investigated the antiproliferative properties of these new compounds on promyelocytic HL-60 leukemia cells by analyzing their effects on cell differentiation, cell cycle progression and apoptosis. SR4 and SR9 were both cytotoxic to HL-60 cells in a dose-and time-dependent manner, with IC(50) of 1.2 μM and 2.2 μM, respectively, after 72 h treatment. Both compounds s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…Similarly, an AMPK activator, AICAR, has been recently reported to induce G1/S cell cycle arrest and inhibit proliferation in cancer cells (35). We also observed cell cycle arrest in human leukemia melanoma and lung and breast cancer cells (19,20, unpublished data). Overall, these data indicate that COH-SR4 induction of AMPK in both adipocytes and cancer cells results in cell cycle arrest, and thus, imply a common molecular target.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Similarly, an AMPK activator, AICAR, has been recently reported to induce G1/S cell cycle arrest and inhibit proliferation in cancer cells (35). We also observed cell cycle arrest in human leukemia melanoma and lung and breast cancer cells (19,20, unpublished data). Overall, these data indicate that COH-SR4 induction of AMPK in both adipocytes and cancer cells results in cell cycle arrest, and thus, imply a common molecular target.…”
Section: Discussionsupporting
confidence: 79%
“…A recent study showed that chemicals that can cause depolarization of mitochondrial membrane potential (Δψm) can also activate AMPK (32). Interestingly, we previously found that COH-SR4 decreased Δψm in HL-60 leukemia cells (19). We are currently investigating the effects of COH-SR4 on the mitochondria to identify the exact molecular target of the compound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SR4 was synthesized according to a previously validated protocol at the Chemical GMP Synthesis Facility, Translational Medicinal Chemistry Laboratory, Beckman Research Institute of the City of Hope (30). FCCP, antimycin A, rotenone, 6-ketocholestanol (6-KCH), cyclosporin A (CSA), bongkrekic acid, N,N,NЈ,NЈ-tetramethyl-p-phenylenediamine (TMPD), valinomycin, ascorbic acid, malic acid, succinate, MitoTempo, guanosine diphosphate (GDP), N-acetyl-L-cysteine (NAC), fatty acid/endotoxin-free bovine serum albumin (BSA), tetramethylrhodamine ester (TMRE), 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT), and crystal violet (CV) were purchased from Sigma.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%